2023
DOI: 10.1192/j.eurpsy.2023.2474
|View full text |Cite
|
Sign up to set email alerts
|

Postmarket safety profile of suicide/self-injury for GLP-1 receptor agonist: a real-world pharmacovigilance analysis

Congqin Chen,
Rijing Zhou,
Fang Fu
et al.

Abstract: Background Recent reports of individuals experiencing suicidal and/or self-injurious behaviors while using liraglutide and semaglutide have heightened the concerns regarding neuropsychiatric safety of Glucagon-like peptide-1 agonists (GLP-1RAs). As real-world evidence is very limited, we explored the association between GLP-1RA and suicide/self-injury by mining the FDA Adverse Event Reporting System (FAERS) database. Methods The FAERS database was queried from 2005 Q2 to 2023 Q2. The Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 54 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…The majority of SSIB cases reported in the current RCT and post-marketing study are not considered to be related to GLP-1 RAs. The disproportionate analyses conducted concurrently with our study, based on the FAERS database with varying year spans, also indicate no direct association between GLP-1RAs and SSIBs [ 55 , 56 ]. In a retrospective analysis utilizing electronic health records, researchers noted that semaglutide can even reduce the risk of suicide compared to non-GLP-1 RAs anti-obesity medications [ 57 ].…”
Section: Discussionmentioning
confidence: 84%
“…The majority of SSIB cases reported in the current RCT and post-marketing study are not considered to be related to GLP-1 RAs. The disproportionate analyses conducted concurrently with our study, based on the FAERS database with varying year spans, also indicate no direct association between GLP-1RAs and SSIBs [ 55 , 56 ]. In a retrospective analysis utilizing electronic health records, researchers noted that semaglutide can even reduce the risk of suicide compared to non-GLP-1 RAs anti-obesity medications [ 57 ].…”
Section: Discussionmentioning
confidence: 84%
“…The evidence evaluating this risk is meagre. Few recent studies have questioned this association [ 9 , 10 , 11 ], and no study has compared this risk between different GLP-1 RAs. Clinical trials have several limitations related to their duration and patient inclusion criteria that can impede investigations on psychiatric adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Some concerns have been raised among healthcare professionals over the safety profiles of GLP-1 Ras. There have been reports of suicidal or self-injurious behaviors (SSIBs) to the European Medicines Agency (EMA), although pharmacovigilance reviews have reported no direct link between GLP-1 RAs and SSIBs ( Chen et al, 2023 ; Chen et al, 2024 ; Zhou et al, 2024 ). Increased risks of thyroid cancer and cholecystitis have been reported ( He et al, 2022 ; Bezin et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%